Optimization of the Combination Ratio of Biduri and Bidara Leaf Extracts in Reducing Cholesterol in Mice - Jazilatur Rifqiyah; Cicik Wijayanti; Gaby Ayu Patricia; Siti Nur Husnul Yusmiati; Khoirul Ngibad (Justek : Jurnal Sains dan Teknologi, 2025)
This study aimed to evaluate the effectiveness of a combination of ethanol extracts of Biduri (Calotropis gigantea L.) and Bidara (Ziziphus spina-christi L.) leaves in reducing cholesterol levels in mice induced with hypercholesterolemia, as well as to determine the optimal dose and combination ratio. This experimental laboratory study involved several stages, including extract preparation, preparation of extract suspensions, preparation of simvastatin and propylthiouracil (PTU) suspensions, selection and maintenance of experimental animals, administration of treatments, and measurement of blood cholesterol levels. A total of 72 male mice were divided into 12 treatment groups: negative control, positive control, drug control, and nine groups receiving combinations of extracts with ratios of 1:1, 1:2, and 2:1 at three doses (14, 28, and 56 mg/20 g BW). Hypercholesterolemia was induced using PTU for 14 days, followed by oral administration of the extract combinations for 3 days. Cholesterol levels were measured using a spectrophotometer and analyzed using One Way ANOVA. The results showed that the combination of Biduri and Bidara extracts significantly reduced cholesterol levels (p < 0.05), with the highest reduction observed in the 2:1 ratio at a dose of 56 mg/20 g BW, showing a 59.18% decrease (135.47 mg/dL) compared to the positive control. These findings indicate a synergistic effect between the two extracts and suggest their potential as a natural hypocholesterolemic agent.